A Ternary Molten Salt Approach for Direct Regeneration of LiNi0.5Co0.2Mn0.3O2 Cathode. Issue 43 (18th February 2022) - Qin, Zuoyu; Wen, Zuxin; Xu, Yifei; Zheng, Zhicheng; Bai, Mingliang; Zhang, Ning; Jia, Chuankun; Wu, Hao Bin; Chen, Gen
Abstract: Recycling spent lithium‐ion batteries (LIBs) is an urgent task in view of the resource shortage and environmental concerns. Here, a facile ternary molten salt approach is presented for efficiently regenerating the LiNi0.5 Co0.2 Mn0.3 O2 (NCM523) cathode of spent LIBs. Such an approach involves the treatment of spent cathode powder in the ternary molten salt at a moderate temperature (400 °C) and subsequent annealing in oxygen. The Li loss and degraded phases in spent NCM that cause the capacity decay can be fully remedied after the regeneration process. As a result, the regenerated cathode delivers a reversible capacity of 160 mAh g −1 at 0.5 C with retention of 93.7% after 100 cycles and maintains a high capacity of 132 mAh g −1 at a high rate of 5 C. The electrochemical performance of regenerated NCM cathode is compared favorably to the fresh NCM cathode, which demonstrates the feasibility of the molten salt approach to directly regenerate spent NCM cathode. Abstract : A facile ternary molten salt approach for efficiently regenerating the LiNi0.5 Co0.2 Mn0.3 O2 (NCM523) cathode of spent LIBs is presented. The Li loss and phase change within the surface in degraded NCM that cause the capacity decay can be fully remedied after the regeneration process, and the electrochemical performance can be restored.